2004
DOI: 10.1073/pnas.0402014101
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fatty acids enhance nuclear receptor activity through mitogen-activated protein kinase activation and histone deacetylase inhibition

Abstract: In this study, we demonstrate that the pervasive xenobiotic methoxyacetic acid and the commonly prescribed anticonvulsant valproic acid, both short-chain fatty acids (SCFAs), dramatically increase cellular sensitivity to estrogens, progestins, and other nuclear hormone receptor ligands. These compounds do not mimic endogenous hormones but rather act to enhance the transcriptional efficacy of ligand activated nuclear hormone receptors by up to 8-fold in vitro and in vivo. Detailed characterization of their mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 41 publications
(30 reference statements)
9
61
1
Order By: Relevance
“…Kimura et al (3) reported that propionate induced sympathetic activation through the promotion of ERK phosphorylation in sympathetic neurons. Additionally, several SCFAs can potentiate the transcriptional activity of nuclear receptor through the activation of the ERK pathway (23). These findings are consistent with our obtained data.…”
Section: Discussionsupporting
confidence: 93%
“…Kimura et al (3) reported that propionate induced sympathetic activation through the promotion of ERK phosphorylation in sympathetic neurons. Additionally, several SCFAs can potentiate the transcriptional activity of nuclear receptor through the activation of the ERK pathway (23). These findings are consistent with our obtained data.…”
Section: Discussionsupporting
confidence: 93%
“…The latter two examples were associated with robust MAPK activation (48,49), as illustrated herein for the actions of EGF on PR (Fig. 4).…”
Section: Functions Of Liganded Prmentioning
confidence: 61%
“…Recent examples of diverse factors or agents that produce a similar left-ward shift in the doseresponse curve for steroid hormone receptors include the expression of Ubc9 for GR (47), the addition of short-chain fatty acids for ER and PR (48), and constitutively activated Ras signaling for AR (49). The latter two examples were associated with robust MAPK activation (48,49), as illustrated herein for the actions of EGF on PR (Fig.…”
Section: Functions Of Liganded Prmentioning
confidence: 99%
“…However, recent studies have established that EDCs can interfere with hormone signaling through other, indirect mechanisms with effects on nuclear receptors that mediate steroid hormone action (Tabb and Blumberg, 2006). These indirect mechanisms include modulation of coactivator expression (Inoshita et al, 2003;Lonard et al, 2004), alteration of the rate of proteasome-dependent nuclear receptor degradation (Masuyama et al, 2002), changes in DNA methylation (Anway et al, 2005) and hormone sensitization (Jansen et al, 2004). Hormone sensitizing EDCs affect nuclear receptor activity via non-genomic intracellular signaling pathways, and may lead to an increase in the intrinsic transcriptional activity of the receptor without direct interactions between the EDC and the hormone or its receptor.…”
Section: Introductionmentioning
confidence: 99%